Answer:
The answer is 2
Step-by-step explanation:
4z+2y-x
4(4)+2(-6)-2
16+(-12)-2
16-12-2
4-2
2
Answer:
6.
Step-by-step explanation:
This is [p(2+h)) - p(2) ] / ((2 + h - 2)
= [ 6(2) + h) + 7 - (6(2) + 7)] / h
= ( 12 + 6h + 7 - 12 - 7) / h
= 6h / h
= 6.
Answer:
Julio did 6/2. The correct answer is 12.
Step-by-step explanation:
6/1/2=6*2=12. Julio forgot to change the division into multiplication. Dividing is multiplying by it's reciprocal.
Same thing as before!
First, we can get rid of d(x) simply by looking at it because we can tell it's linear (it's a straight line). If we look at the table, we can see a(x) is also linear because it has a steady rate of growth. b(x) and c(x) both represent exponential growth. The curved shape of b(x) shows us this is exponential growth, and the exponent in c(x) tells us it's also exponential.
Answer:
Option (D). G(x) = x³ - x
Step-by-step explanation:
Given function is the attachment,
G(x) = (x - 1.5)³ - (x - 1.5)
This function when translated by left by 1.5 units, rule for the translation is,
G(x) → G'(x + 1.5)
Therefore, translated function will be,
G'(x) = (x - 1.5 + 1.5)³ - (x - 1.5 + 1.5)
G'(x) = x³ - x
Therefore, Option (D) will be the answer.